The Development of Value Co-creation of New Retail in Taian City, The People's Republic of China - Lei, Wang; Teerapornlertratt, Preyaporn; Phuvakeereevivat , Ariya; Kumboon, Buraporn (International Journal of Multidisciplinary in Management and Tourism, 2023)
The Internet has become an integral part of people and businesses. Others have adapted by bringing the Internet into use in the organization to increase the efficiency of business operations. This Article aimed to study (1) the difference between Offline and Online retail in theory and approach (2) the development of new retail in TAIAN City (3) the reasons that influence the value co-creation of new retail model in TAIAN City and (4) the directional suggestions for the development of new retail in TAIAN City. It is quantitative and qualitative research; The sample was 400 samples. The questionnaire was used for quantitative research. and qualitative research through in-depth interviews with 20 department managers. The analysis of basic data adopts content such as frequency, percentage, mean, standard deviation, etc. and the second part is model analysis, which uses A-mode structural equation statistical analysis. The research results were found as follows; 1. Online retail and offline retail have a positive impact on the development of new retail. 2. In the process of development, producers and consumers are no longer competitors, and they use the concept of value co-creation to achieve maximum benefits. 3. Online retail utilizes more efficient communication and convenient services to make consumers feel needed and respected and participate in value co-creation together. 4. Value co-creation serves as an intermediate bridge to promote the development of new retail, actively guiding the integration of online retail and offline retail, and promoting the development of new retail. It was concluded that in modern retail Online sales and offline sales should be developed in order to be successful and maximize the benefit of all parties. The concept of creating value must be brought together and there must be effective communication in order to provide good service to customers.